Optimizing Vector Control Programs to Reduce Dengue Fever (DHF) Cases - Surya Darma; Panjaitan, Delita Hayanti; Ginting, Rosita (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Dengue Hemorrhagic Fever (DHF) remains a public health problem in Indonesia, including in Tebing Tinggi City. Vector control efforts are carried out through various strategies, including Mosquito Nest Eradication (PSN), the use of larvicides (abatesation), and insecticide spraying (fogging). This study aims to evaluate the implementation of the vector control program in the working area of ​​the Rambung Tebing Tinggi Community Health Center (UPT). The research method uses a qualitative approach through in-depth interviews, observations, and document reviews. Research informants include the head of administration, program officers, mosquito larvae control cadres, and the community. Data analysis was carried out through reduction, presentation, and drawing conclusions. The results show that the PSN is routinely implemented by mosquito larvae control cadres through mosquito larvae surveys, with the support of community health center officers and cross-sectoral collaboration. Abatesation is carried out by distributing abate powder to residents' homes accompanied by education regarding safe use. Fogging is carried out selectively based on the results of epidemiological investigations and has received a positive response, although it is considered only a short-term solution. In general, the vector control program at the Rambung Community Health Center is running quite well, but increased public awareness regarding environmental hygiene and reduced reliance on fogging are needed. Collaboration between health workers, cadres, and the community is key to the success of sustainable dengue control.